212k views
3 votes
Simplify the following expression. (3m/4-2)+8

A. 8m/4
B. 9m/4
C. 3m+24/4
D. 3m+28/4

Simplify the following expression. (3m/4-2)+8 A. 8m/4 B. 9m/4 C. 3m+24/4 D. 3m+28/4-example-1

1 Answer

4 votes

Answer:

C. 3m+24/4

Explanation:

Given that (3m/4 - 2) + 8

Then we solve

= (3m/4 - 8/4) + 8

= (3m - 8)/4 + 32/4

= (3m - 8 + 32)/4

= 3m + 24 /4

Therefore the answer is C

Alternatively, we can simplify the equation by

Given that, the equation is ( 3m/4 - 2 ) + 8

We then remove parenthesis

= 3m/4 - 2 + 8

= 3m/4 + 6

= 3m/4 + 24/4

Then add the numerators and leave the denominator

= 3m + 24 /4

This also equals option C.

Hence, it can be concluded that, the correct answer is Option C: (3m + 24)/4

User Akatakritos
by
4.8k points